France between the alliance of the Ottoman Empire and the hostility of Algeria -1535-1830- - Cherchali , Zakia (Journal of Social Sciences and Humanities, 2020)
The nature of Franco-Ottoman relations reflected a clear contradiction, because the ally of the sublime Porte which declared a friendship and alliances to him for a long time. And concluded a series of treaties to ensure their continuity, is the same France which declared its hostility towards Algeria. One of the most important Ottoman provinces. And sought to carry out several military campaigns against it. And even if French plans to share Ottoman lands remained secret over the centuries, his hostility towards Algeria reflected his true intentions towards the Ottoman Empire. This research aims to demonstrate the duality of discourse in Franco-Ottoman relations, using the analysis of the crises of the eastern question. We looked at the assembly of Algeria to the Ottoman Empire. This research aims to demonstrate the duality of discourse in Franco-Ottoman relations, using the analysis of the crises of the eastern question. And the Franco-Ottoman relations through which the government of Paris announced its friendship. We have also touched on France's defensive opinions towards the Franco-Ottoman wars and its attempts to preserve its existence On the other hand, we approached Franco-Ottoman relations through which we clarified the secret projects that France implemented for the sharing of the Ottoman provinces, as well as Franco-Algerian relations which demonstrated the different aspects of the confrontation between the two parties. Then the plans for the occupation of Algeria and the expedition to Algiers. Finally the Franco-Ottoman relations after the expedition which reflected a very surprising relationship of good understanding. In the end, we demonstrated the real reasons for France's peaceful declarations in contradiction with its colonial plans, thus testifying to its historical hypocrisy.